Learning a Second Language in Adulthood Changes Subcortical Neural Encoding. (21st October 2020) - Liu, Dongxin; Wang, Shuo; Gao, Qi; Dong, Ruijuan; Fu, Xinxing; Pugh, Esther; Hu, Jiong
Abstract : Second language learning has been shown to impact and reshape the central nervous system, anatomically and functionally. Most of the studies on second language learning and neuroplasticity have been focused on cortical areas, whereas the subcortical neural encoding mechanism and its relationship with L2 learning have not been examined extensively. The purpose of this study was to utilize frequency-following response (FFR) to examine if and how learning a tonal language in adulthood changes the subcortical neural encoding in hearing adults. Three groups of subjects were recruited: native speakers of Mandarin Chinese (native speakers (NS)), learners of the language (L2 learners), and those with no experience (native speakers of foreign languages (NSFL)). It is hypothesized that differences would exist in FFRs obtained from the three language experience groups. Results revealed that FFRs obtained from L2 learners were found to be more robust than the NSFL group, yet not on a par with the NS group. Such results may suggest that in human adulthood, subcortical neural encoding ability may be trainable with the acquisition of a new language and that neuroplasticity at the brainstem level can indeed be influenced by L2 learning.